Constrained controllability of retarded dynamical systems - Klamka, Jerzy (1944- ) (Zielona Góra: Uniwersytet Zielonogórski)
Recent years have witnessed a good deal of research focused on abstract control dynamical systems defined in infinite-dimensional linear spaces. The main purpose of the present paper is to study the concept of constrained approximate relative and approximate absolute controllability for linear stationary abstract retarded dynamical systems defined in infinite-dimensional Hilbert spaces.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka